Impact of hand-foot skin reaction on treatment outcome in patients receiving capecitabine plus erlotinib for advanced pancreatic cancer: A subgroup analysis from AIO-PK0104. (July 2015) - Kruger, Stephan; Boeck, Stefan; Heinemann, Volker; Laubender, Ruediger P.; Vehling-Kaiser, Ursula; Waldschmidt, Dirk; Kettner, Erika; Märten, Angela; Winkelmann, Cornelia; Klein, Stefan; Kojouharoff, Georgi; Gauler, Thomas C.; et al.
Abstract Background. Drug-induced skin toxicity may correlate with treatment efficacy in cancer patients receiving chemotherapy or biological agents. The correlation of the capecitabine-associated hand-foot skin reaction (HFS) on outcome parameters in pancreatic cancer (PC) has not yet been investigated. Methods. Within the multicentre phase III AIO-PK0104 trial, patients with confirmed advanced PC were randomly assigned to first-line treatment with either capecitabine plus erlotinib (150 mg/day, arm A) or gemcitabine plus erlotinib (150 mg/day, arm B). A cross-over to either gemcitabine (arm A) or capecitabine (arm B) was performed after failure of the first-line regimen. Data on skin toxicity were correlated with efficacy study endpoints using uni- and multivariate analyses. To control for guarantee-time bias (GTB), we focused on subgroup analyses of patients who had completed two and three or more treatment cycles. Results. Of 281 randomised patients, skin toxicity data were available for 255 patients. Median time to capecitabine-attributed HFS was two cycles, 36 of 47 (77%) HFS events had been observed by the end of treatment cycle three. Considering HFS during first-line treatment in 101 patients treated with capecitabine for at least two cycles within the capecitabine plus erlotinib arm, time to treatment failure after first- and second-line therapy (TTF2) and overall survival (OS) both were significantly prolonged for the 44 patients (44%) with HFS compared to 57 patients without HFS (56%) (TTF2: 7.8 vs. 3.8 months, HR 0.50, p = 0.001; OS: 10.4 vs. 5.9 months, HR 0.55, p = 0.005). A subgroup analysis of 70 patients on treatment with capecitabine for at least three cycles showed similar results (TTF2: 8.3 vs. 4.4 months, HR 0.53, p = 0.010; OS: 10.4 vs. 6.7 months, HR 0.62, p = 0.056). Conclusion. The present subgroup analysis from AIO-PK0104 suggests that HFS may serve as an independent clinical predictor for treatment outcome in capecitabine-treated patients with advanced PC.